Anisotropic stratification beneath Africa from joint inversion of SKS and P receiver functions - (:unkn) unknown (My University, 2010)
The analysis of rock anisotropy revealed by seismic waves provides fundamental constraints on stress-strain field in the lithosphere and asthenosphere. Nevertheless, the anisotropic models resolved for the crust and the upper mantle using seismic waves sometimes show substantial discrepancies depending on the type of data analyzed. In particular, at several permanent stations located in Africa, previous studies revealed that the observations of SKS splitting are accounted for by models with a single and homogeneous anisotropic layer whereas 3-D tomographic models derived from surface waves exhibit clear anisotropic stratification. Here we tackle the issue of depth-dependent anisotropy by performing joint inversion of receiver functions (RF) and SKS waveforms at four permanent broadband stations along the East African Rift System (EARS) and also on the Congo Craton. For three out of the four stations studied, stratified models allow for the best fit of the data. The vertical variations in the anisotropic pattern show interesting correlations with changes in the thermomechanical state of the mantle associated with the lithosphere-asthenosphere transition and with the presence of hot mantle beneath the Afar region and beneath the EARS branches that surround the Tanzanian Craton. Our interpretation is consistent with the conclusion of earlier studies that suggest that beneath individual stations, multiple sources of anisotropy, chiefly olivine lattice preferred orientation and melt pocket shape preferred orientation in our case, exist at different depths. Our study further emphasizes that multiple layers of anisotropy must often be considered to obtain realistic models of the crust and upper mantle.
Keywords: African Research